2021
DOI: 10.1111/hdi.12949
|View full text |Cite
|
Sign up to set email alerts
|

Is home hemodialysis a practical option for older people?

Abstract: An increasing demand for in-center dialysis services has been largely driven by a rapid growth of the older population progressing to end-stage kidney disease. Since the onset of the COVID-19 pandemic, efforts to encourage homebased dialysis options have increased due to risks of infective transmission for patients receiving hemodialysis in center-based units. There are various practical and clinical advantages for patients receiving hemodialysis at home. However, the lack of caregiver support, cognitive and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The prevalence of caregiver overburden when taking care of an older adult receiving dialysis is variable across published observational studies, with this being reported as high as 85% [ 92 , 93 ]. Family members of older patients receiving home dialysis may require full-time employment for financial sustainability, and taking up caregiver roles and responsibilities simultaneously may lead to caregiver burnout [ 94 ]. Caregivers for older patients receiving home dialysis may also be older individuals themselves with chronic illness, and this responsibility could add further physical and psychological burden [ 94 ].…”
Section: Supporting Older Adults Who Are Receiving Home Dialysismentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of caregiver overburden when taking care of an older adult receiving dialysis is variable across published observational studies, with this being reported as high as 85% [ 92 , 93 ]. Family members of older patients receiving home dialysis may require full-time employment for financial sustainability, and taking up caregiver roles and responsibilities simultaneously may lead to caregiver burnout [ 94 ]. Caregivers for older patients receiving home dialysis may also be older individuals themselves with chronic illness, and this responsibility could add further physical and psychological burden [ 94 ].…”
Section: Supporting Older Adults Who Are Receiving Home Dialysismentioning
confidence: 99%
“…Family members of older patients receiving home dialysis may require full-time employment for financial sustainability, and taking up caregiver roles and responsibilities simultaneously may lead to caregiver burnout [ 94 ]. Caregivers for older patients receiving home dialysis may also be older individuals themselves with chronic illness, and this responsibility could add further physical and psychological burden [ 94 ]. Qualitative studies reported low mood in a significant proportion of family members caring for patients on nocturnal PD and HHD [ 88–91 ].…”
Section: Supporting Older Adults Who Are Receiving Home Dialysismentioning
confidence: 99%
See 1 more Smart Citation